Prevalence and Progression of Chronic Kidney Disease in Adult Patients With Sickle Cell Disease. (1st June 2014) - Gosmanova, Elvira O.; Zaidi, Sahar; Wan, Jim Y.; Adams-Graves, Patricia E.
Abstract : Aim: We evaluated the prevalence and progression of chronic kidney disease (CKD) during the 5-year period in a cohort of patients with sickle cell disease (SCD) aged 18 years and older. Methods: We studied 98 patients with SCD. Chronic kidney disease stages I through V were defined based on estimated glomerular filtration rate (eGFR), and albuminuria grades were defined based on spot urine protein-to-creatinine ratio according to the 2012 Kidney Disease Improving Global Outcomes recommendations. In patients with eGFR of greater than 60 mL/min per 1.73 m 2, CKD was diagnosed if grade A2 or A3 albuminuria was present. Chronic kidney disease progression was defined as an increase in CKD stage with an additional eGFR reduction of more than 25% from baseline. Results: At baseline, 28.6% of patients had CKD. After a mean follow-up of 5.0 (SD, 0.9) years, 17 patients developed new CKD and the overall CKD prevalence increased to 41.8%. In addition, 8 patients experienced CKD progression. The following baseline variables were associated with the development and progression of CKD in univariate analysis: older age ( P = 0.003), higher systolic blood pressure (BP; P = 0.003), lower eGFR ( P = 0.001), higher serum creatinine ( P = 0.001), and A3 albuminuria ( P = 0.008). In multivariate analysis, baseline A3 albuminuria (adjusted odds ratio, 5.0; 95% confidence interval, 1.1-24.3; P = 0.048) and each 1-mm Hg increase in systolic BP (adjusted odds ratio, 1.04; 95% confidence interval, 1.0-1.07; P = 0.039) predicted CKD development and progression. Conclusions: Chronic kidney disease is common in patients with SCD and its prevalence increases with age. Several baseline modifiable and nonmodifiable factors were associated with the development and progression of CKD in patients with SCD. Strategies targeting BP control and proteinuria may be beneficial for individuals with SCD.